The Place the Competency-based Approach of Education in the Educational Management System - Olga V. Fokina; Andrey A. Kolupaev; Artem A. Yarovenko; Anna I. Guseva; Olga V. Ignatyeva (International Review of Management and Marketing, 2016)
The article based on the analysis of the literature sources and experience in the field of economic education at Polytechnic Institute examined the system of key concepts on the subject, as well as the role of the introduction of competence-based approach in teaching practice of Polytechnic Institute with a view to efficient management of the learning process. The article describes training method aimed at formation of key information and technological competences of the future economic expert, the process of psycho-pedagogical testing of students and teachers on proprietary methodology. On the basis of personal data and observations discovered are some tendencies and clarified are the conditions of computer training of future specialists in economics, as well as the need for further experimental study of pedagogical factors and relationships. The experiment allowed solving one of the main tasks of modern education which is developing the necessity for continuous updating of knowledge, accumulating the experience in getting new interdisciplinary knowledge, formation the communication skills of students.